2012
DOI: 10.1108/09590551211263164
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of online shopping in India: shopping orientation segments

Abstract: Purpose -This study aims to explore Indian online shopping via the concept of shopping orientations. Design/methodology/approach -Surveys were collected from 536 consumer panel members. Online shopping segments were identified by using a two-step process that clustered respondents in terms of the similarity of their scores across four shopping orientations. Findings -Three segments were identified: value singularity, quality at any price, and reputation/recreation. The quality at any price and reputation/recre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 31 publications
(33 reference statements)
4
65
0
Order By: Relevance
“…Similar factors were found for online users in United States (Swinyard and Smith, 2003) and also for China by Ye et al (2011). However, there is dearth of such studies in the Indian context (Gehrt et al, 2012). Hence, the objectives of this study are twofold:…”
Section: Objectives Of This Studymentioning
confidence: 51%
See 2 more Smart Citations
“…Similar factors were found for online users in United States (Swinyard and Smith, 2003) and also for China by Ye et al (2011). However, there is dearth of such studies in the Indian context (Gehrt et al, 2012). Hence, the objectives of this study are twofold:…”
Section: Objectives Of This Studymentioning
confidence: 51%
“…They also found that touch and feel as well as financial risk is an important factor underlying the customer's reluctance to buy expensive products online and product expensiveness was inversely related to future purchase intentions. Gehrt et al (2012) found very few shopping orientations of Indian shoppers as compared to other countries, namely, value orientation, quality with convenience orientation, recreation orientation and reputation with convenience orientation. They therefore strongly argued for the need to do further research to reveal Indian consumers' perceptions of the marketplace.…”
Section: E-lifestylesmentioning
confidence: 89%
See 1 more Smart Citation
“…Measurement model analysis indicated that navigation characteristics of websites followed by website design and security and privacy are the significant dimensions of website functionality. Gehrt et al, 2012). This indicates security and privacy protection is an important driver influencing online purchase.…”
Section: Discussionmentioning
confidence: 99%
“…The results also indicated perceived credibility risk defined by security risk and privacy risk to be significantly negatively related to behavioural intention demonstrating that these concerns are important in deterring customers from using mobile commerce. Gehrt et al (2012) explored the Indian online shopping orientations based on sample of 538 consumer panel members. Three shopping orientation segments were identified: value singularity, quality at any price, and reputation/recreation.…”
Section: Relevant Antecedent Factors In Indian Contextmentioning
confidence: 99%